2013
DOI: 10.1016/j.ntt.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal cocaine exposure on child behavior and growth at 10years of age

Abstract: We examined physical growth and behavioral outcomes in 226 10-year-old children who were participants in a longitudinal study of prenatal cocaine exposure (PCE), while controlling for other factors that affect development. During the first trimester, 42% of the women used cocaine, with use declining across pregnancy. At the 10-year follow-up, the caregivers were 37 years old, had 12.8 years of education, and 50% were African American. First trimester cocaine exposure predicted decreased weight, height, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 87 publications
2
26
0
5
Order By: Relevance
“…Growth restriction among prenatal cocaine exposure children has been documented to continue well past infancy (Minnes et al, 2006) and may persist in children as old as 10 years of age (Covington et al, 2002;Richardson et al, 2013). While consistency exists in the reports of reduced fetal growth and development, some follow-up studies at later ages have suggested catch-up growth.…”
Section: Cocainementioning
confidence: 99%
“…Growth restriction among prenatal cocaine exposure children has been documented to continue well past infancy (Minnes et al, 2006) and may persist in children as old as 10 years of age (Covington et al, 2002;Richardson et al, 2013). While consistency exists in the reports of reduced fetal growth and development, some follow-up studies at later ages have suggested catch-up growth.…”
Section: Cocainementioning
confidence: 99%
“…La EPC perturba el desarrollo de los procesos biológicos y sumada a un ambiente adverso, tanto intrauterino como posnatal, produce diversas alteraciones en el PSICOLOGÍA http://dx.doi.org/10.21615/cesp.10.1.5 desarrollo físico (Eyler et al, 2009;Lambert & Bauer, 2012;Morrow et al, 2009); cognoscitivo -atención, aprendizaje/memoria, lenguaje- (Henry et al, 2007;Magri et al, 2007;Morrow et al, 2009;Linares et al, 2006), y emocional (Coleman et al, 2014;Davis & Pfaff, 2014;Haagen, 2014;Lucantonio, Stalnaker, Shaham, Niv, & Schoenbaum, 2012;Moisiadis & Matthews, 2014;Richardson, Goldschmidt, Larkby, & Day, 2013), que persisten a lo largo de la vida.…”
Section: Introductionunclassified
“…Existen numerosos estudios que muestran que los descendientes de padres adictos tienen alta probabilidad de llegar a ser adictos en la adolescencia o juventud temprana, tanto en animales como en humanos (Estelles et al, 2006;Glantz & Chambers, 2006;Malanga et al, 2007;Minnes et al, 2014;Richardson et al, 2013;Rocha et al, 2002).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Los hijos de madres adictas a la cocaína presentan numerosas alteraciones en áreas emocionales, cognitivas, motrices y conductuales, tales como la ansiedad o la depresión, dificultades en la respuesta del estrés, problemas en la regulación afectiva, inestabilidad, irritabilidad, déficit atencional, desorden desafiante oposicional, labilidad, anorexia y vulnerabilidad al consumo de drogas (Ackerman, Riggins & Black, 2010;Bennett, Bendersky & Lewis, 2007;Coleman, Liu, Oguz, Styner & Crews, 2014;Chaplin et al, 2014;Hancock & Grant, 2009;Kippin, Campbell, Ploense, Knight & Bagley, 2015;Lambert & Bauer, 2012;Lester et al, 2012;Lucantonio, Stalnaker, Shaham, Niv & Schoenbaum, 2012;Minnes et al, 2014;Richardson, Goldschmidt, Larkby & Day, 2013;Sinha, 2008).…”
Section: Introductionunclassified